2003
DOI: 10.1182/blood-2002-08-2652
|View full text |Cite
|
Sign up to set email alerts
|

Evi3, a common retroviral integration site in murine B-cell lymphoma, encodes an EBFAZ-related Krüppel-like zinc finger protein

Abstract: Retroviral insertional mutagenesis in inbred mouse strains provides a powerful method for cancer gene discovery. Here, we show that a common retroviral integration site (RIS) in AKXD B-cell lymphomas, termed Evi3, encodes a novel zinc finger protein with 30 Krü ppel-like zinc finger repeats. Most integrations at Evi3 are located upstream of the first translated exon and result in 3 long-terminal repeat (LTR)-driven overexpression of Evi3. Evi3 is highly related to the early B-cell factorassociated zinc finger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 18 publications
5
94
0
Order By: Relevance
“…We obtained 21% identity and 50% similarity (Fig. 1a), in spite of a reduced number of 21 ZF domains compared to the 29-30 ZFs present in vertebrates Reed 1997, 1998;Hata et al 2000;Warming et al 2003Warming et al , 2004. We also confirmed that DmOAZ is the unique OAZ member in the fruit fly.…”
Section: Sequence Analysis Of a Putative D Melanogaster Oaz Homologuesupporting
confidence: 69%
See 1 more Smart Citation
“…We obtained 21% identity and 50% similarity (Fig. 1a), in spite of a reduced number of 21 ZF domains compared to the 29-30 ZFs present in vertebrates Reed 1997, 1998;Hata et al 2000;Warming et al 2003Warming et al , 2004. We also confirmed that DmOAZ is the unique OAZ member in the fruit fly.…”
Section: Sequence Analysis Of a Putative D Melanogaster Oaz Homologuesupporting
confidence: 69%
“…The function of the ZF 1 was not yet characterized. By summarizing the different studies on OAZ family members, we noted that this organization was conserved Reed 1997, 1998;Hata et al 2000;Shim et al 2002;Ku et al 2003;Warming et al 2003Warming et al , 2004. To structurally analyze the DmOAZ protein, we determined the arrangement of the 21 ZFs in four clusters by using Simple Modular Architecture Research Tool software (http://smart.embl-heidelberg.de; Schultz et al 1998;Letunic et al 2004), and we aligned each DmOAZ cluster on the entire sequence of the orthologues.…”
Section: Sequence Analysis Of a Putative D Melanogaster Oaz Homologuementioning
confidence: 99%
“…Zfp521 was originally identified as a retroviral integration site in AKXD mice with B-lineage lymphomas, which encodes a transcription factor with multiple zinc-fingers (Warming et al, 2003). Although the molecular mechanisms by which aberrant expression of Zfp521 contributes to leukemogenesis are not fully understood, one possibility is that Zfp521 impairs normal B-cell development by inhibiting the function of EBF1 (Hentges et al, 2005), a transcription factor required for B-cell development (Lin and Grosschedl, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Three translocations were identified (PAX5-ETV6, 56,57 PAX5-FOXP1, PAX5-ZNF521), each of which fuses the DNA-binding paired domain of PAX5 to key functional domains of partner genes that have known or putative roles in lymphoid development or oncogenesis. [58][59][60][61][62] These translocations are predicted to disrupt normal activity of PAX5 (and possibly the partner gene), and in luciferase reporter assays using a CD19 reporter, the fusions were found to act as competitive inhibitors of normal PAX5 transactivating activity. Subsequent studies have identified additional PAX5 fusions in ALL, involving multiple partner genes including ASXL1, AUTS2, BRD1, C20orf112, DACH1, ELN, HIPK1, JAK2, KIF3B, LOC392027, PML, POM121 and SLCO1B3.…”
Section: Mutations Of Genes Regulating B-lymphoid Development In Allmentioning
confidence: 99%